Study of deep level parameters in a silicon diode using capacity-based deep level transient spectroscopy - Aimaganbetov, K.P.; Tokmoldin, N.S. (Recent Contributions to Physics, 2017)
Defects occurring in semiconductor materials have a significant impact on their electrophysical properties (conductivity, lifetime of charge carriers). In the case of energy levels of the defects being located within the band gap of these materials, far from the edges of the valence and conduction bands, they are also known as “deep levels”. Defects appearing within the band gaps of semiconductor materials may be both intrinsic and result from external technological factors. Parameters characterizing deep levels include ionization energy, concentration and cross-section. These parameters may be comprehensively using capacity-based deep level transient spectroscopy («deep level transient spectroscopy» DLTS). The main advantage of this technique is its high sensitivity enabling to study the band gap structure in semiconductor materials. This paper describes the methodology of using deep level transient spectroscopy for the characterization of a KD208A silicon diode with the purpose of identifying and studying deep level characteristics in this device.